2010
DOI: 10.1177/070674371005500807
|View full text |Cite
|
Sign up to set email alerts
|

La SUMD (Scale to Assess Unawareness of Mental Disorder): Validation et adaptation française dans une population de patients souffrant de schizophrénie

Abstract: Objectifs : L'objectif principal a été de mener la validation française de la Scale to Assess Unawareness of Mental Disorder (SUMD) auprès d'une population souffrant de schizophrénie.Méthode : Cent patients souffrant de troubles schizophréniques ont été inclus. Nos analyses statistiques ont évalué la fidélité inter-juges, la validité théorique, la validité convergente ou divergente. Finalement, une analyse factorielle exploratoire a été conduite. Résultats :Nos résultats montrent que la version francophone de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Although a large number of insight instruments have already been validated for patients with schizophrenia, their process of validation has often used small study samples. For example, the validation of the long version of the SUMD was initially conducted using 43 patients [17] and more recently using 100 patients [60]. The ITAQ was validated among 52 patients [2], the ISP among 30 patients [56], and the IS among 43 [57] and 64 patients [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of insight instruments have already been validated for patients with schizophrenia, their process of validation has often used small study samples. For example, the validation of the long version of the SUMD was initially conducted using 43 patients [17] and more recently using 100 patients [60]. The ITAQ was validated among 52 patients [2], the ISP among 30 patients [56], and the IS among 43 [57] and 64 patients [58].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inter-judge reliability is an important property for expert-rating scales such as the SUMD. Previous studies have, however, shown a satisfactory inter-judge reliability for the long version of the SUMD [17,60]. Sensitivity to change is also of particular interest for patient follow-ups in clinical practices and should thus be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Insight was assessed using both self-report (Birchwood Insight Scale, BIS [24,25]) and clinician-rated (Scale to assess Unawareness of Mental Disorder, SUMD [26,27]) scales, as recommended [28]. Higher BIS scores and lower SUMD scores indicate better insight.…”
Section: Methodsmentioning
confidence: 99%
“…The SUMD evaluates insight into various dimensions of the disease across the following independent dimensions: presence of mental disorders, need for treatment, presence of signs and symptoms. The SUMD [3,41] is a standardized scale that relies on a direct interview with the patient. For our study, we choose to ask participants on their current insight to answer the three general items evaluating insight with regard to mental disorders, and the items on awareness and attribution of hallucinations and delusions.…”
Section: Evaluation Scalesmentioning
confidence: 99%